POTRET WACANA INTEGRASI DALAM PEMBERITAAN TENTANG DUGAAN PENISTAAN AGAMA DI KEPULAUAN BANGKA BELITUNG - Muslim Ansori (Prodi Jurnalistik Islam IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2021)
The main focus of this paper is on Integrated Discussion Analysis in Publication Concerning Suspection of religious defamation of Daud Rafles in West Bangka. Religious communities in Bangka Belitung definitely need integration in order to create religious harmony. However, in the intensity of interaction and certain situations, friction will occur even though it is on a small scale and can still be minimized. Conflict control in Bangka Belitung can be carried out because of the large potential for integration in society. This potency has been growing and developing for a long time together with the patterns of dynamic society. Starting from the reflection on the publication of bangka.tribunnews.com concerning the case of religious defamation in West Bangka, it can be concluded, First, according to media perspective, the integrated discussion in the news framing of bangka.tribunnews.com is preferred, although it must cover the point of view with facts that have higher news value. Second, the discourse is crystallized in several certain points of view (angle). Third, it is not enough, the point of view referred to is detailed in the title, lead, news, conclusion or closing statement , and other related matters. Some of the technical elements of publication have to be interconnected, even between news items in one topic must also be related. Thus, the publication will further strengthen religious harmony in Bangka Belitung. This conclusion is supported by certain discourse points of view, such as using the point of view of the perpetrator who is strongly suspected of being proven guilty, religious defamation behavior should get serious offense , the police should be responsive, the judicial process is quite smooth, the peaceful message and respects the legal process that is running from the Indonesian Ulema Council ( MUI) Bangka Belitung, and the Religious Communication Forum (FKUB)